The Protective Effects of γ-Tocotrienol on Muscle Stem Cells Through Inhibiting Reactive Oxidative Stress Production - Yang, Shuo; Yang, Juan; Zhao, Huiwen; Deng, Rong; Fan, Hancheng; Zhang, Jinfu; Yang, Zihao; Zeng, Huihong; Kuang, Bohai; Shao, Lijian (Frontiers in Cell and Developmental Biology, 2022)
Pseudotrophic muscular dystrophy is a common clinical skeletal muscle necrotic disease, among which Duchenne muscular dystrophy (DMD) is the predominant. For such diseases, there is no clinically effective treatment, which is only symptomatic or palliative treatment. Oxidative stress and chronic inflammation are common pathological features of DMD. In recent years, it has been found that the pathophysiological changes of skeletal muscle in DMD mice are related to muscle stem cell failure. In the present study, we established a DMD mice model and provided tocotrienol (γ-tocotrienol, GT3), an antioxidant drug, to explore the relationship between the physiological state of muscle stem cells and oxidative stress. We found that the application of GT3 can reduce ROS production in the muscle stem cells of DMD mice, which is beneficial to promote the recovery of muscle stem cell function in DMD mice. These data suggest that increased ROS production causes dysfunctional muscle stem cell in DMD mice, which might provide a new avenue to treat DMD patients in the clinic.